Analysis of the effect of economic growth toward the center of the overflow area and hinterlend in determining nodal centre of new growth on the area of Mamminasata in South Sulawesi - Zainuddin Rahman (Indonesia Prime, 2017)
This research conducted in Mamminasata District, South Sulawesi Province. This study examines the Economic Effects of the overflow "Pertuhan Against Nodal regions and Hinterland. The purpose of this research is: (1) to review the impact of the effects of development and economic growth of the overflow against Nodal regions and Hinterlan in a region (Maminasata), (2) to examine and explain the impact of the overflow against labor, enterprise development, (3) to examine and explain the strategy and Policy Development areas in South Sulawesi.The research method used was diskriptif by using model ratio analysis. The population was throughout the County and the city in South Sulawesi while the sample is selected by pusposive, i.e., Mamminasata Area that includes the city of Makassar, Maros Regency Gowa (Minasa), Takalar Regency. The data of the secondary data is yangdigunakan by taking data for the year 2011-2013.The research results showed that the distance of the Centre of the region with growth has an impact on the magnitude of the effect of abundance that can be received by each region, where the overflow effect of Gowa received a big growth 8.689810974, Maros 4.05005707, Takalar Regency. 2.344019694. While the new growth Centre in the area of the District Mamminasata Takalar. A development strategy that can do is how to build synergy with neighboring derah so economic abundance can flow into the area that synergizes